ANALISIS PRAKTIK MANAJEMEN RISIKO PADA PT.BANK PERKREDITAN RAKYAT(BPR) DANA PENSIUN(DP) TASPEN - Andhiny GM; Wibowo Wibowo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
This study aimed to analyze and evaluate the risk management practices at BPR is currently growing. What risk management practices have been well managed and has been in accordance with the financial services authority rules. The method used is descriptive method. The primary data of the questionnaire used in this study are obtained from the employees who worked at PT BPR DP TASPEN. Sampling is done by Convenience sampling method in order to obtain the total sample of 20 respondents. The analysis method used in this research is descriptive statistical analysis and to test the questionnaire study is to test the validity and reliability testing. Data processing is conducted by using SPSS 13. The study delivers that the risk management at PT BPR DP TASPEN are adequate and in compliance with the financial services authority rules. In addition, this study also concludes that the risk management at PT BPR DP TASPEN has been managed well.